THU0368 Dosage Reduction of Biological Therapy in Patients with Axial Spondyloarthritis in Persistent Clinical Remission. (23rd January 2014) - Almirall, M.; Salman, T. C.; Lisbona, M. P.; Iniesta, S.; Maymó, J.
Abstract : Background: The effectiveness of TNF blockers in treating axial Spondyloarthritis patients is well know, but we don't know most appropriate dosage for treatment of patients in persistent clinical remission. Objectives: Our objective is to assess the clinical activity at 3 and 6 months in patients with axial Spondyloarthritis in persistent remission who received low dosages of biological therapy. Methods: We performed a observational study with patients of our department with axial Spondyloarthritis including Ankylosing Spondylitis who received low dosages of TNF blockers until September 2012 by persistent remission (BASDAI≤2, absence of arthritis and enthesitis and normality of CRP values) for a minimum of 6 months without NSAIDs consume. Data analysed were: demographic characteristics, duration of clinical remission, diagnosis and disease duration, type and duration of biological agent used and at 3 and 6 months: percentage of patients who remained in remission (BASDAI≤2), percentage who had low disease activity (BASDAI between 2 and 4 units) and percentage who relapsed (BASDAI≥4) and required the previous dose of biological treatment. Results: We included 40 patients (75% man) with a mean age of 43, 7+/- 13 years and a mean time of remission of 28, 7 +/- 18, 5 months. The diagnoses were: 33 Ankylosing Spondylitis, 5 non-radiographic axial Spondyloarthritis and 2 Spondyloarthritis associated with bowel inflammatory disease. They had a mean duration of disease of 8, 6+/- 6, 1 years and 75% of patients had HLAB27 positive. 7 patients received Etanercept, 7 Infliximab and 26 Adalimumab and a mean duration of current biological therapy was 41, 9 +/- 23, 9 months. Used low dosages was 50 mg every 10 days or 25 mg every week for Etanercept, 3mg/kg every 8 weeks for Infliximab and 40 mg every 3 weeks for Adalimumab. All 40 patients had a minimum follow-up of 3 months after dosage reduction. At 3 months 85% of patients remained in remission, 10% had low disease activity and 5% relapsed (2). 24 patients were followed for 6 months after dosage reduction. At 6 months 71% remained in clinical remission, 12, 5% had low disease activity and 16, 5% relapsed (4), 2 at 3 months and 2 at 6 months. Conclusions: Most of our patients with axial Spondylarthritis remained in clinical remission at 3 and 6 months after after dosage reduction of TNF blockers. Only a small percentage of the patients relapsed and required the previous dosage of biological treatment. Disclosure of Interest: None Declared